2020
DOI: 10.3390/cells9030711
|View full text |Cite
|
Sign up to set email alerts
|

miR-7 Controls the Dopaminergic/Oligodendroglial Fate through Wnt/β-catenin Signaling Regulation

Abstract: During the development of the central nervous system, the proliferation of neural progenitors and differentiation of neurons and glia are tightly regulated by different transcription factors and signaling cascades, such as the Wnt and Shh pathways. This process takes place in cooperation with several microRNAs, some of which evolutionarily conserved in vertebrates, from teleosts to mammals. We focused our attention on miR-7, as its role in the regulation of cell signaling during neural development is still unc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 56 publications
1
13
0
Order By: Relevance
“…In this study, we identified TCF12 as a target of miR‐7 in C2C12 cells. This is consistent with the results of Adusumilli, who found that miR‐7 targeted TCF12 in human neural progenitor cells involved in neural development (Adusumilli et al, 2020). The protein encoded by TCF12 (also known as HEB ) is a member of the basic helix‐loop‐helix (bHLH) E‐protein family, which is expressed in many tissues, such as skeletal muscle, thymus, B‐ and T‐cells (Massari & Murre, 2000).…”
Section: Discussionsupporting
confidence: 92%
“…In this study, we identified TCF12 as a target of miR‐7 in C2C12 cells. This is consistent with the results of Adusumilli, who found that miR‐7 targeted TCF12 in human neural progenitor cells involved in neural development (Adusumilli et al, 2020). The protein encoded by TCF12 (also known as HEB ) is a member of the basic helix‐loop‐helix (bHLH) E‐protein family, which is expressed in many tissues, such as skeletal muscle, thymus, B‐ and T‐cells (Massari & Murre, 2000).…”
Section: Discussionsupporting
confidence: 92%
“…Since miR‐7a has a variety of targets other than Pax6 , especially in the central nervous system, it might have other effects beyond the regulation of Pax6 and neurogenesis. For example, miR‐7a controls the balance between oligodendroglial and dopaminergic neuronal cell fates by inhibiting Wnt signaling and facilitating Shh signaling, 39 which might account for the depression‐like effects of OPRK1 agonists. Besides, the neural protective effect of miR‐7a was discovered by a series of studies, as it was able to inhibit neuronal apoptosis and oxidative stress in oxygen‐glucose deprivation (OGD) model, 40,41 and to ameliorate ischemic damage 42 .…”
Section: Discussionmentioning
confidence: 99%
“…miR-125b and miR-181 appear to specifically promote the differentiation of hESCs towards the DA fate, because the percentage of TH + cells is enhanced by the ectopic expression of these two miRNAs [64]. Conversely, in vitro studies on hESCs evidenced that the overexpression of miR-7a led to a decrease of TH + neurons by altering the balance between Wnt and Shh signaling and consequently promoting the switch to glial cell populations; coherently, its knockdown increases the number of DA neurons [65]. Similarly, the hyperexpression of miRNA-124 led to a reduction of TH + neurons.…”
Section: Mirna-mediated Control Of Differentiation and Maintenance Of Da Neuronsmentioning
confidence: 98%